Analisis Pengaruh Keterlibatan Pengguna dan Dukungan Pengawas Mengenai Kinerja Sistem Informasi Akuntansi di Bank Syariah Mandiri Yogyakarta. - M Samsul Haidir (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
Abstract: The purpose of this study is to conduct empirical testing and analysis of user involvement and supervisor support, regarding the performance of accounting information systems at independent Islamic bank of Yogyakarta. This type of research is field research and uses quantitative methods. Where in this study using 50 respondents. The results of the study revealed that user involvement in the development of the system has a significant difference, so that user involvement has an influence in terms of the performance of accounting information systems while the support of supervisors also has a significant influence on the performance of accounting information systems in the independent Islamic bank in Yogyakarta. Therefore, the need for support from all stackholders to continue to improve the quality of service of the information system itself to be more compatible in the future.